Avaliação da sustentabilidade ambiental nos institutos federais - Hecktheuer, Daniel Almeida (2012)
The environmental management has reached a highlight in discussions in different sectors in the society and the sustainable development has become an indispensable subject about development policies. Associated to that, Learning Institutions perform an important role in forming new generations. Environmental education aims at developing the awareness of the need to worry about matters related to the environment and the search of alternatives for the existing problems, creating agents in the prevention of environmental problems. The general objective of this work was to evaluate the Environmental Sustainability of the Federal Institutes of Education, Science and technology from Brazil and to propose directions for the Sul-rio-grandense Federal Institute campus Passo Fundo, with the intention of subsidizing actions, goals and policies of sustainability. The research method sought to investigate, by means of direct mail, the 333 Federal Institutions in the country. A return of 99 questionnaires was obtained, pointing to the existing environmental indicators in the institution. The results do not show a tendency of behavior of the Federal Institutions by region. By the analysis of the aspect, it is highlighted a greater participation among to the related to the teaching and research, consumption materials, solid residue, energy, and incentive to collective transportation. The proposed directions for the Federal Institute campus Passo Fundo - have the objective of not only improving what already exists but also innovating, creating, and pondering new solutions that take sustainability to the institution